Hadith #2243 - Sunan Abi Dawud - Abdul Hameed bin Ja'far عبد الحميد بن جعفر بن عبد الله; Ibrahim bin Musa al-Razi al-Fara' إبراهيم بن موسى الرازي الفراء; Isa bin Yonus bin Abi Ishaq عيسى بن يونس بن أبي إسحاق; Ja'far bin 'Abdullah جعفر بن عبد الله بن الحكم (Sunan Abi Dawud)
I said: Messenger of Allah, I have embraced Islam and two sisters are my wives. He said: Divorce any one of them you wish.
Grade: Hasan

Hadith #3115 - Sunan Abi Dawud - Abdul Hameed bin Ja'far عبد الحميد بن جعفر بن عبد الله; Kathir bin Marrah al-Hadrami كثير بن مرة الحضرمي; Mu'adh ibn Jabal; Salah bin Abi Aryb صالح بن أبي عريب (Sunan Abi Dawud)
The Messenger of Allah (ﷺ): When you attend dying man, you should say good words, for the angels say Amin to what you say. When Abu Salamah died, I said: What should I say, Messenger of Allah? He said: O Allah forgive him, and give us something good in exchange. She said: So Allah gave me Muhammad (ﷺ) in exchange for him.
Grade: Sahih

Hadith #3314 - Sunan Abi Dawud - Abdul Hameed bin Ja'far عبد الحميد بن جعفر بن عبد الله; Abu Bakr al-Hanfi عبد الكبير بن عبد المجيد- أبو بكر الحنفي; Amr bin Shu'aib bin Muhammad عمرو بن شعيب بن محمد السهمي; Kardam bin Sufyan al-Thaqafi; Maymuna bin Kardam; Muhammad bin Bashar Bindar محمد بن بشار بندار (Sunan Abi Dawud)
I went out with my father to see the hajj performed by the Messenger of Allah (ﷺ). I saw the Messenger of Allah (ﷺ). I fixed my eyes on him. My father came near him while he was riding his she-camel. He had a whip like the whip of scribes. I heard the bedouin and the people say: The whip, the whip. My father came near him and held his foot. She said: He admitted his Prophethood and stood and listened to him. He said: Messenger of Allah, I have made a vow that if a son is born to me, I shall
Grade: Sahih

Hadith #3486 - Sunan Abi Dawud - Abdul Hameed bin Ja'far عبد الحميد بن جعفر بن عبد الله; al-Dahhak bin Mukhlad Abu 'Asim al-Nabil الضحاك بن مخلد أبو عاصم النبيل; Jabir ibn 'Abdullah; Muhammad bin Bashar Bindar محمد بن بشار بندار; Yazid bin Abi Habib يزيد بن أبي حبيب (Sunan Abi Dawud)
That he heard the Messenger of Allah (ﷺ) say in the year of the Conquest when he was in Mecca: Allah has forbidden the sale of wine, animals which have dead natural death, swine and idols. He was asked: Messenger of Allah, what do you think of the fat of animals which had died a natural death, for it was used for caulking ships, greasing skins, and making oil for lamps? He replies: No, it is forbidden. Thereafter, the Messenger of Allah (ﷺ) said: May Allah curse the Jews! When Allah declared
Grade: Sahih